The Effects of Price Perceptions, Food Quality, and Menu Variations on Ordering Decisions and Their Impact on Customer Loyalty in Online Culinary Products - Rahayu Lestari; Tiara Pradani; Kumba Digdowiseiso (Budapest International Research and Critics University, 2022)
This study aims to investigate whether perceptions of price, quality of food, and menu variations have a significant effect on ordering decisions and their impact on customer loyalty in online culinary products among Millennials. Our study put more emphasize on improving the ordering decisions and consumer loyalty in culinary businesses. We utilize a Purposive Sampling technique, with as many as 100 respondents using proportional random sampling. The analytical method used is statistical-partial least squares by incorporating SPSS Version 24.00 and SmartPLS 3.0 software. The results showed that price perception had an insignificant effect on ordering decisions. In addition, food quality had a positive and significant effect on ordering decisions. Meanwhile, menu variations produced an insignificant effect on ordering decisions. Similarly, menu variations showed an insignificant effect on ordering decisions. Price perception had a positive and significant effect on customer loyalty, while both food quality and menu variations had an insignificant effect on customer loyalty. Ordering decisions had a positive and significant effect on customer loyalty.